Radiofrequency echographic multi-spectrometry for early bone health: The REMS-bone study protocol (Trial acronym: REMS-bone) - Serafina Perrone; Malgorzata Wasniewska; Maria-Elisabeth Street; Virginia Beretta; Elena Scarpa; Chiara Petrolini; Andrea Dall’Asta; Domenico Corica; Tommaso Aversa; Giorgia Pepe; Letteria Morabito; Federica Grassi; et al. (Global Pediatrics)
Background: Bone health begins with maternal health and nutrition, which influences skeletal mass and bone mineral density (BMD) already in utero. Maximization of bone mass during skeletal growth has become the goal of primary prevention of osteopenia and osteoporosis. The amount of bone gained during growth and its subsequent rate of loss are closely linked to the final skeletal mass in adulthood. Radiofrequency Echographic Multi Spectrometry (REMS) technology has proven to be useful in the assessment of BMD in pregnant women. However, the feasibility of REMS for the assessment of bone status in newborns remains unknown. This multicenter longitudinal study aims at using REMS to evaluate skeletal status in fetuses, newborns and children until 12 months of age. Methods: Two hundred mother-newborn dyads, with infants born at term of gestation, will be consecutively recruited during the prenatal period and followed up until 12 months of life. BMD will be assessed with REMS technology in mothers, fetuses, newborns and infants at 1, 3 6 and 12 months of life. In all enrolled patients, blood will be collected at specific time points and oxidative stress biomarkers, specific microRNAs, and several bone metabolites will be measured in blood, whereas endocrine disruptors will be measured in urine. Discussion: This study is designed to provide robust data on the best method to identify and evaluate bone status starting from intrauterine life. The associations among BMD, maternal nutrition, early exposure to endocrine disruptors, and other investigated molecules will also be investigated in relationship with subsequent body composition and bone health. Trial registration: The protocol was retrospectively registered on ClinicalTrials.gov on December 3rd, 2024, with the ID number NCT06750523.